Ex-ante evaluation of public-private partnerships: Macroeconomic analysis - Liu, J.; Love, Peter; Carey, B.; Smith, J.; Regan, M. (American Society of Civil Engineers (ASCE), 2015)
© 2014 American Society of Civil Engineers. Public-private partnerships (PPPs) are currently a popular approach for governments to procure social and economic infrastructure. The macroeconomic environment plays a critical role and influences the factors that can lead to the successful delivery of a PPP project. Despite the importance of the macroeconomic environment, limited attention has been paid to ex-ante (that is, before the event, or forecast) evaluation. A review of the normative literature was undertaken, aiming to derive key performance indicators (KPIs) of PPP success. The KPIs were validated by using a vector error correction model. It is suggested that the developed KPIs can be used to evaluate the suitability of the macroeconomic conditions in which a PPP project will be implemented. These KPIs can provide governments and stakeholders with a platform to conduct an effective ex-ante evaluation of PPP projects that will be significant in policy and decision making.